Implementasi teori the seven pillars of information literacy sconul dalam menganalisis kemampuan literasi informasi masyarakat Kelurahan Pattallassang - Lukman Lukman; Dian Muhtadiah Hamna; A Nurul Fatimah Azzahra (Berkala Ilmu Perpustakaan dan Informasi, 2024)
Introduction. Information literacy is one of the keys to improve the quality of human resources. This study aims to determine the level of information literacy of the Pattallassang Village community and obtain solutions to optimize problems related to information literacy in the community. Data Collection Methods. We collected the data using a quantitative descriptive approach. The data collection technique was carried out by distributing questionnaires. There were 80 respondents participated as a result of an accidental sampling. Data Analysis. The research variable used was information literacy skills with indicators of the seven pillars of information literacy theory by the Standing Conference of National and University Libraries. The data analysis technique was descriptive resulted by the Likert scale. Results and Discussion. Referring to the seven pillars of information literacy, the average score of Pattallassang Village community information literacy level showed a moderate category. Solutions to optimize the problem, namely community education, is recommended to the government to form community information groups by providing anti-hoax information media platforms. Conclusion and Suggestion. Implementing information literacy in life is very important in the current era. Research related to information literacy in society needs to be carried out by providing education to support sustainability.